Chondroblastic osteosarcoma in a feline: a case report - Dalmagro, Mirian Juliana; Silva, Danby do Nascimento; Matias de Oliveira, Radan Elvis (Brazilian Journal of Case Reports, 2022)
Osteosarcomas are noteworthy as one of the main malignant bone tumors in dogs and cats, comprising an important cause of limb amputation in these species. Literature reports for felines are, however, scarce. Therefore, the aim of the present study was to characterize the clinical and histopathological findings of a chondroblastic osteosarcoma case in a female cat. The chondroblastic osteosarcoma diagnosis was based on radiographic, cytological, histopathological and immune-histochemical findings. Clinical, radiographic, and cytological findings suggested a presumptive osteosarcoma diagnosis, while histopathological and immune-histochemical findings confirmed a chondroblastic osteosarcoma diagnosis.